Eight-week flywheel training enhances jump performance and stretch-shortening cycle function in collegiate basketball players - Shimizu, T.; Tsuchiya, Y.; Ueda, H.; Izumi, S.; Ochi, E. (European Journal of Sport Science, 2025)
The effects of flywheel (FW) training on jump performance, muscle function, and muscle mass in athletes have not been fully clarified. The purpose of the present study was to evaluate the effects of an 8-week FW training program on jump performance, stretch-shortening cycle (SSC) function, muscle strength, peak power and muscle thickness in collegiate basketball players. Twenty male college basketball players (mean age: 19.8 ± 1.3 years, height: 179.1 ± 6.7 cm, body mass: 72.9 ± 6.3 kg) were randomly assigned to either the FW training (n = 11) or control group (n = 9). The FW training group performed squat exercises, 5 sets of 8 repetitions, twice a week using the FW device. Baseline and post-training assessments of jump heights of squat jumps (SJs), countermovement jumps (CMJs), and drop jumps (DJs) were performed in both groups. Additionally, the reactive strength index (RSI), representing SSC function; isometric maximum voluntary contraction (MVC) torque during knee joint extension; peak power during squats; and quadriceps muscle thickness were evaluated. As the results, we observed that the FW training group demonstrated significant increases in post-training SJ height (15.1%, p = 0.03), DJ height (23.2%, p = 0.01), RSI (36.8%, p = 0.04), MVC, peak power and muscle thickness compared with pre-training levels. Furthermore, between-group comparisons indicated significantly higher post-training SJ height, DJ height, RSI, MVC, peak power, and muscle thickness in the FW training group (p < 0.05). Therefore, the FW training program effectively enhanced jump performance and SSC function in male basketball players and proved beneficial for muscle strength and hypertrophy.